The Role of Self-Control in Mediating the Influence of Social Media Use and Peer Environment on Consumptive Behavior in Senior High School Students in Bekasi City - Novanti, Anissa Rizki; Saptono, Ari; Pratama, Aditya (The Future of Education Journal, 2024)
This study aims to determine the effect of social media use and peer environment on consumer behavior mediated by self-control. The population in this study were students of State Senior High Schools in Bekasi City with the accessible population being students of SMAN 1 Bekasi City, SMAN 2 Bekasi City, and SMAN 3 Bekasi City with a research sample of 301 students. Data were collected through questionnaires which were then analyzed using the Smart PLS 3.2.9 application. The results of this study indicate that: 1) The use of social media has a positive and significant effect on consumer behavior; 2) The peer environment has a positive and significant effect on consumer behavior; 3) The use of social media has a negative and significant effect on self-control; 4) The peer environment has a negative and significant effect on self-control; 5) Self-control has a negative and significant effect on consumer behavior; 6) Self-control does not mediate the effect of social media use on consumer behavior and; 7) Self-control does not mediate the effect of peer environment on consumer behavior.